1992
DOI: 10.1159/000118904
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatment and Memory Assessment: Methodology

Abstract: Clinical observations have suggested that lithium may exert adverse effects on memory. The difficulty in achieving empirical consensus regarding this issue has reflected several methodological problems: diversity of research designs, heterogeneous samples, lack of control groups and the possible confounding of memory test scores by variables such as depression, other acute psychopatho-logies, organicity, treatment duration, and age. The diversity of memory tests in terms of the complexity and modality of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Lithium has been reported to impair memory in humans (Engelsmann et al, 1992), including verbal learning (Pachet and Wisniewski, 2003). Our previous data showed that pretraining administration of lithium-induced memory impairment in an inhibitory avoidance task in mice (Zarrindast et al, 2005.…”
Section: Discussionmentioning
confidence: 90%
“…Lithium has been reported to impair memory in humans (Engelsmann et al, 1992), including verbal learning (Pachet and Wisniewski, 2003). Our previous data showed that pretraining administration of lithium-induced memory impairment in an inhibitory avoidance task in mice (Zarrindast et al, 2005.…”
Section: Discussionmentioning
confidence: 90%
“…Lithium is commonly used for treatment of BPD and levels need to be regularly monitored to avoid toxicity, a serious condition that can cause marked and possibly enduring neurocognitive deficits (45). However, at therapeutic levels, findings of adverse effects on neurocognitive performance have been contradictory (46). In addition, few studies have examined the effects of lithium and other BPD medications (adverse or beneficial) on role functioning while controlling for the effects of other antipsychotic medications, an additional source of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Although in one of our previous studies lithium at a dose of 5 mg/kg induced amnesia, in that study lithium was administered before the training session of the inhibitory avoidance task [30] . The drug has been shown to cause adverse effects on memory in humans [3,4,34] . Inhibition of the enzyme inositol monophosphatase by lithium [35,36] , and/or its effect on cAMP [37][38][39][40] and/or G-proteins [6,41,42] have been suggested to be possible mechanisms involved in the effect of lithium.…”
Section: Discussionmentioning
confidence: 99%